Magnetic Mitohormesis as a Potential Non-Invasive Restorative Therapy for X-Linked Muscular Dystrophies - Jan Nikolas Iversen; Alfredo Franco-Obregón (International Journal of Molecular Sciences, 2026)
Duchenne and Becker X-linked muscular dystrophies are no longer viewed as disorders arising solely from passive sarcolemmal fragility but as diseases that progress because of disruption of cellular mechanotransduction. Evidence is accumulating that the gating of TRPC1 and TRPC3 mechanosensitive channels is altered in the absence of dystrophin, resulting in a breakdown of sarcoplasmic calcium homeostasis and preferential loss of type II glycolytic muscle fibres, while type I oxidative fibres are spared. TRPC1-mediated Ca2+ influx is known to activate the calcineurin–NFAT pathway, upregulating PGC-1α transcriptional activity to promote mitochondriogenesis, antioxidant defences, and the oxidative muscle phenotype. Calcineurin signalling also activates a compensatory pathway in dystrophinless muscle by inducing the expression of utrophin, a dystrophin autosomal homologue, capable of substituting for dystrophin at the muscle surface. This perspective explores the possibility that non-mechanical biophysical stimuli can be used to restore calcineurin signalling by non-invasively activating TRPC1. Pulsed electromagnetic field (PEMF) exposure has been shown to stimulate TRPC1-mediated Ca2+ entry and calcineurin-dependent signalling in skeletal muscle and may serve as a gentle method to induce utrophin expression in X-linked muscular dystrophies. By activating calcineurin compensatory mechanisms in these disorders, PEMF-based paradigms warrant future investigation as mechanistically grounded adjuvants to conventional therapies.